A study of the public (PSA) on high heel shoes to educate women's health / Nur Illyana Azahari - Azahari, Nur Illyana (2018)
The research explores the relationship between women’s health and wearing high heels, one of women’s accessories and aims to know the affect of wearing high heels. One of these reason , the believe that high heels can give more beautiful, elegant, sexually attractive, additional to some women think that high heel gives their truest. According to The Spine Health Institute, Florida Hospital Medical Group, claim that 72% of women who wore heels at the same point, 77% of women wear heels for special occasion, 50% wear for parties, 33% wear for dancing and 31% wear them for work. Besides that, researcher discovered that high heels actually , alter the natural position of the foot-ankle complex, and thereby produce a chain reaction of affect wearing high heels, especially for women who loves wearing high heel. In this presentation , I will create an awareness campaign and educate women how to wearing high heel in the right way. The campaign aims to bring the awareness and educate women who love to wearing high heel, so that they will concern about the affect when they wear it for working, beauty and etc. Although they will wearing high heels in the right way.